Primary Pulmonary Hodgkin’s Lymphoma - Carrasco-Lozano, Luis Enrique (2022)
We present the case of a 25-year-old woman with a three-month history of cough, fever, dyspnea, pleuritic pain, and a cavitating lesion on chest tomography. She received antituberculous treatment in another health institution without a favorable response. A thoracoscopic biopsy revealed the presence of Reed Sternberg cells consistent with the nodular sclerosis subtype of Hodgkin’s lymphoma. The patient met the criteria for primary pulmonary Hodgkin’s lymphoma, an extremely infrequent and rarely reported entity. A brief review of the literature is carried out.